PENGEMBANGAN POTENSI PARIWISATA PARTISIPATIF BERBASIS MASYARAKAT DI DESA WISATA LALANG, KECAMATAN MANGGAR KABUPATEN BELITUNG TIMUR - Wahyuni Pratiwi Ningsih; Edwin Rizal; Ute Lies Siti Khadijah (Jurnal Inovasi Penelitian, 2022)
A village is said to be advanced, which is inseparable from the characteristics of its local wisdom, people who help each other and support each other in completing a job or in other words, mutual cooperation. Community involvement in the process of tourism development as a process of change is interrelated and cannot be separated, this is of course the main capital in carrying out development in villages to compete in tourism. In the process of tourism development, local communities must participate in all stages starting from the pallning stage implementation to the supervision stage. The purpose of this study was to see the extent to which local communities are involved and participate in the process of developing tourism potential in Lalang Tourism Village, Manggar District, East Belitung Regency. This research uses qualitative descriptive methods, data collection through interviews, field observation using several stages, namely; (a) identification of problems in the development of Lalang Tourism Village, (b) mapping of the potential of Lalang Tourism village, and (c) identification of institutional potential in Lalang Tourism Village.